Enhancing lentiviral production for WAS gene therapy: a comparative analysis of stable producer cell lines evaluating flatware system and adherent bioreactors in perfusion mode - Singh, Parameswari; Lal, Nikki Indresh; Terrao, Monica; Schwingal, Sarah; Biserni, Martina; Aeschimann, Florian; Strauch, Andrea; Dersch, Herbert; Jaramillo, Angel; Gille, Andreas; Laux, Holger (Frontiers in Bioengineering and Biotechnology, 2025)
Ex-vivo gene therapies require scalable, high-quality lentivirus (LV) with excellent transduction efficiency. Achieving this involves a synergistic approach combining efficient vector design and LV process optimization. In our study, we evaluated transfection reagents for generating stable producer cell lines from two Tet-off regulated adherent stable LV packaging PCLs, GPRG and GPRTG, to produce lentivirus (LV) to treat Wiskott Aldrich Syndrome (WAS). Stable producer cell lines expressing the WAS transgene or GFP transgene were generated from GPRG and GPRTG PCLs. The GPRTG producer cell line showed 6-fold higher LV titer and resulted in better transduction of CD34+ cells. Further, we optimized the LV production process in continuous perfusion and recirculation mode and compared three technologies: traditional flatware systems, iCELLis™ Nano and scale-X™ Hydro Univercells adherent bioreactors using GPRTG stable producer cell line. Scale-X™ Hydro outperformed iCELLis™ Nano in LV productivity per surface area (TU/cm2). We successfully scaled up LV production from Scale-X™ Hydro (2.4 m2) to Scale-X™ Carbo (10 m2), producing 1.13E+12 TU per 10 m2 through 7 harvests using the continuous perfusion process. This process produced LV that efficiently transduced CD34+ cells, achieving a vector copy number (VCN) of upto 4 at a Multiplicity of Infection (MOI) of 10. Our study has successfully established a scalable, cost-effective and robust platform for LV production, demonstrating its potential for clinical applications.